Evaluating self-sovereign identity solutions for agricultural supply chains: a systematic review - Alar, Tariq; Bharathy, Gnana; Batra, Usha; Prasad, Mukesh (Frontiers in Blockchain, 2026)
Secure identity solutions are crucial to ensure traceability, transparency, and security for the agricultural supply chain. Ensuring a secure, privacy-preserving, and decentralized identity layer is essential for protecting stakeholders and maintaining trust in increasingly complex agricultural ecosystems. This paper provides a systematic review of Self-Sovereign Identity (SSI) solutions through three stages and guided by five research questions (RQs) that guide the assessment and evaluation process. Initially, 1,229 articles were retrieved from multiple scientific databases, and 78 primary studies were selected according to predefined inclusion and exclusion criteria. Although blockchain has been widely studied for traceability, limited work has explicitly evaluated SSI frameworks within agricultural supply chains, revealing a significant gap in identity-focused research. This review assesses the current state of digital identity solutions, with a particular focus on those that utilize blockchain technology for agricultural supply chains. These solutions are evaluated based on the essential principles of self-sovereign identity—transparency, privacy and protection, user control, and decentralization. The findings indicate that while no existing SSI solution fully satisfies all the essential criteria for agricultural supply chains, Sovrin emerges as the most promising framework, excelling particularly in decentralization and privacy protection. The review concludes by identifying key research gaps, outlining deployment-oriented recommendations, and highlighting the need for real-world pilot studies to validate the operational effectiveness of blockchain-based SSI systems in agricultural supply chains.